PEMODELAN SPASIAL KESESUAIAN HABITAT BURUNG ENGGANG GADING (Rhinoplax vigil) DI KAWASAN CAGAR ALAM GUNUNG NYIUT KABUPATEN BENGKAYANG - Hendra Budaya Hadikusuma; Siti Latifah; Erianto Erianto (Tengkawang : Jurnal Ilmu Kehutanan, 2023)
Helmeted Hornbills bird (Rhinoplax Vigil) are increasingly threatened by illegal hunting, trade activities, and deforestation. Rhinoplax Vigil is listed in Appendix I of CITES (endangered and prohibited to be traded), and protected according to Law No. 5 of 1990 concerning Conservation of Biological Resources and their Ecosystems, and PP No. 7 of 1999 concerning Preservation of Plant and Animal Types. We have been protecting its existence or to perform conservation of Helmeted Hornbills is to make spatial modeling habitat suitability of Helmeted Hornbills. Spatial modeling is an activity which makes a spatial model of a phenomenon, spatial modeling can be done using a Geographic Information System (GIS). This study aims to create a spatial model of an Rhinoplax Vigil habitat suitability map in the Nyiut Mountain Nature Reserve area of Bengkayang Regency, West Kalimantan Province. Spatial modeling using ArcMap 10.5 software. The result of interpolation between Rhinoplax Vigil  to height, slope, NDVI, distance from the river, road and settlement shows the level of agreement needed by the Rhinoplax Vigil  , including the dominance of the meeting point on the altitude at an altitude of 500 m above sea level, while the slope shows a slope of 15-25%, NDVI shows a value of 0,3 – 0,4 in a fairly tight vegetation condition, the distance from the river is generally found in the range of 0 - 2 Km. the distance from the road and settlements is precisely the Rhinoplax Vigil  away which is dominant at a distance of 6 - 8 Km. PCA (Principal Component Analysis) analysis results explain that by using two main components can explain the variant as much as 70,676%, the weight of each variable has a value of Y = (2,940 x Fk Settlement) + (2,940 x Fk Road) + (1,300 x Fk Rivers) + (2,940 x Fk Elevation) + (1,300 x FkSlope) + (1,300 x FkNDVI). Validation value of the high suitability has an area of 13,975 hectares with a validation percentage of 87%, for the medium level of suitability has an area of 15,051 hectares with a validation percentage of 10%, while for low suitability shows in an area of 10,391 hectares with validation of 3%. Keywords: GIS, Helmeted Hornbill, Habitat, Spatial Modeling                            AbstrakBurung Enggang (Hornbills helmeted) semakin terancam oleh kegiatan berburu liar,  perdagangan ilegal, dan deforestasi . Burung Rangkong termasuk dalam Lampiran I CITES (terancam punah dan dilarang diperdagangkan), dan dilindungi sesuai dengan UU No. 5 Tahun 1990 tentang Konservasi Sumberdaya Hayati dan Ekosistemnya, dan PP No. 7 tahun 1999 tentang pelestarian jenis tumbuhan dan hewan. Salah satu cara untuk melindungi keberadaan atau melakukan konservasi burung Enggang Gading adalah membuat pemodelan spatial kesesuaian habitat burung Enggang Gading.  Pemodelan spasial adalah kegiatan yang membuat model spasial suatu fenomena, pemodelan spasial dapat dilakukan dengan menggunakan Geographic Information System (GIS). Penelitian ini bertujuan membuat pemodelan spasial peta kesesuaian habitat burung Enggang Gading di wilayah Cagar Alam Gunung Nyiut, Kabupaten Bengkayang, Provinsi Kalimantan Barat. Pemodelan spasial menggunakan perangkat lunak ArcMap 10,5. Hasil interpolasi antara data kelas ketinggian (dpal), kelas kemiringan lereng, nilai indeks vegetasi (NDVI), kelas jarak lokasi dari sungai, kelas jarak lokasi dari jalan dan kelas jarak lokasi dari permukiman. Burung Enggang Gading memerlukan habitat dengan ketinggian  500 m di atas permukaan laut, pada kemiringan 15-25%, NDVI menunjukkan nilai 0, 3 – 0, 4 dalam kondisi vegetasi yang cukup rapat , jarak dari Sungai umumnya ditemukan di kisaran 0-2 km jarak dari jalan dan permukiman jarak dari lokasi habitat adalah 6-8 km.Hasil analisis PCA (Principal komponen Analysis) menjelaskan bahwa dengan menggunakan dua komponen utama mempunyai keragaman kumulatifmya 70.676%, bobot setiap variabel memiliki nilai Y = (2.940 x FK Settlement) + (2.940 x FK jalan) + (1.300 x FK sungai) + (2.940 x FK elevasi) + (1.300 x FkSlope) + (1.300 x FkNDVI).Berdasarkan nilai validasi, nilai kesesuaian yang tinggi seluas 13.975 hektar dengan persentase validasi 87%, untuk tingkat menengah kesesuaian luas 15.051 hektar dengan persentase validasi 10%, sedangkan untuk kesesuaian rendah  luas wilayah 10.391 hektar dengan validasi 3%. Kata kunci : SIG, Burung Enggang Gading, habitat, Pemodelan spatial